2021
DOI: 10.3389/fmicb.2021.665001
|View full text |Cite
|
Sign up to set email alerts
|

How Do Shipworms Eat Wood? Screening Shipworm Gill Symbiont Genomes for Lignin-Modifying Enzymes

Abstract: Shipworms are ecologically and economically important mollusks that feed on woody plant material (lignocellulosic biomass) in marine environments. Digestion occurs in a specialized cecum, reported to be virtually sterile and lacking resident gut microbiota. Wood-degrading CAZymes are produced both endogenously and by gill endosymbiotic bacteria, with extracellular enzymes from the latter being transported to the gut. Previous research has predominantly focused on how these animals process the cellulose compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 95 publications
0
8
0
Order By: Relevance
“…Until now, most cellulose-active enzymes have been isolated and characterised from wood-decaying fungi and soil bacteria [6][7][8][9]. Cellulose-degrading higher organisms may use symbiotic microbes as a source of enzymes for biomass degradation, such as the marine shipworm which is an eminent lignocellulose degrader [10][11][12], remain largely unexplored. In the present study, we analysed marine wood-digesting bivalve molluscs called shipworms, which feeds on submerged wood in the ocean.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, most cellulose-active enzymes have been isolated and characterised from wood-decaying fungi and soil bacteria [6][7][8][9]. Cellulose-degrading higher organisms may use symbiotic microbes as a source of enzymes for biomass degradation, such as the marine shipworm which is an eminent lignocellulose degrader [10][11][12], remain largely unexplored. In the present study, we analysed marine wood-digesting bivalve molluscs called shipworms, which feeds on submerged wood in the ocean.…”
Section: Introductionmentioning
confidence: 99%
“…However, later it was reported that endosymbiotic bacteria residing in a specialized region of the gill tissue have been shown to x atmospheric nitrogen [15] but also produce variety of carbohydrate active enzymes (CAZymes) that function in lignocellulose deconstruction in shipworms [16]. In addition to this, shipworms themselves also produce several endogenous CAZymes that are secreted by a specialized digestive gland that nally accumulate in cecum for lignocellulose digestion [10,11]. Because of these unique features, shipworms are an attractive target for the discovery of new CAZymes for depolymerization of lignocellulose.…”
Section: Introductionmentioning
confidence: 99%
“…However, later it was reported that endosymbiotic bacteria residing in a specialized region of the gill tissue have been shown to fix atmospheric nitrogen [15] but also produce variety of carbohydrate active enzymes (CAZymes) that function in lignocellulose deconstruction in shipworms [16]. In addition to this, shipworms themselves also produce several endogenous CAZymes that are secreted by a specialized digestive gland that finally accumulate in cecum for lignocellulose digestion [10, 11]. Because of these unique features, shipworms are an attractive target for the discovery of new CAZymes for depolymerization of lignocellulose.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, most cellulose-active enzymes have been isolated and characterised from wood-decaying fungi and soil bacteria [6][7][8][9]. Cellulosedegrading higher organisms may use symbiotic microbes as a source of enzymes for biomass degradation, such as the marine shipworm which is an eminent lignocellulose degrader [10][11][12], remain largely unexplored. In the present study, we analysed marine wood-digesting bivalve molluscs called shipworms, which feeds on submerged wood in the ocean.…”
Section: Introductionmentioning
confidence: 99%
“…However, later it was reported that endosymbiotic bacteria residing in a specialized region of the gill tissue have been shown to fix atmospheric nitrogen [ 15 ] also produce variety of carbohydrate active enzymes (CAZymes) that function in lignocellulose digestion in cecum of shipworms [ 16 ]. In addition, shipworms produce several endogenous CAZymes secreted by a specialized digestive gland that finally accumulate in cecum for lignocellulose digestion [ 10 , 11 ]. Because of these unique features, shipworms are an attractive target for the discovery of new CAZymes for depolymerization of lignocellulose.…”
Section: Introductionmentioning
confidence: 99%